Circulating Intercellular Adhesion Molecule-1 (cICAM-1) Concentration in Liver Disease: Relationship with Cholestasis and Functioning Hepatic Mass. Issue 5 (14th January 2016) - Pirisi, Mario; Falleti, Edmondo; Fabris, Carlo; Soardo, Giorgio; Toniutto, Peluigi; Vitulli, Daniela; Pezzetta, Francesca; Bortolotti, Nadia; Gonano, Fabio; Bartoli, Ettore
Abstract : The authors measured immunoenzymatically circulating intercellular adhesion molecule-1 (cICAM-1) concentration in 135 patients with liver disease of either viral or toxic etiology: 13 had acute hepatitis; 58 had mild chronic liver disease; and 64 had cirrhosis (superimposed in 30 by hepatocellular carcinoma). Forty patients with extrahepatic diseases (19 with malignancies) and 28 healthy blood donors were tested as controls. One-way analysis of variance demonstrated a significant variability of cICAM-1 concentration among groups (F = 76.67, P <; .0001), the highest value being recorded in acute hepatitis (Bonferroni's test for pairwise comparisons, P < .01). Total bilirubin showed a strong correlation with cICAM-1 (R = 0.766, P < .001). By stepwise multiple regression analysis the independent predictors of clCAM-1 concentration were chosen in the following order: total bilirubin; aspartate aminotransferase; cholinesterase; alpha-1-antitrypsin; and immunoglobulins. Thus, in addition to inflammation, cholestasis and decline of functioning hepatic mass may influence cICAM-1 concentration.